Al-Islam dan kemuhammadiyahan sebagai basis pendidikan karakter - Baidarus Baidarus; Tasman Hamami; Fitriah M. Suud; Azam Syukur Rahmatullah (Universitas Muhammadiyah Ponorogo, 2020)
Muhammadiyah is one of the world's largest mass Muslim organizations that have developed education in Indonesia. In particular, in the city of Pekanbaru Muhammadiyah was built by several schools. As one of the organizations that care about education, Muhammadiyah also highlights the role of state character. The aim of this research is to see how Islamic and Kemuhamadiyahan lessons in several high schools in the city of Pekanbaru to build the character of the students. This research is expected to be able to contribute to the organizations involved in helping to realize a nation of character through education in the school's guidance. The study uses a qualitative method by the phenomenology approach. The research informants were 65, consisting of school principals, vice-principals, teachers and students.